2020
DOI: 10.21606/drs.2020.193
|View full text |Cite
|
Sign up to set email alerts
|

Design Education for the Knowledge Society: An Action Research Study of Implementing a Liberal Arts Approach to Industrial Design Education

Abstract: This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License. 1. Education for Economic Growth or Human Development? Trends in higher education have led educationists and academics to argue that design education has come to function as an alternative form of general liberal arts education (Buchanan, 1992, p. 5). Now students might choose to study design as they might choose to study the humanities and arts, that is, without the intention to pursue design as a career (Schön… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In general design education, researchers suggested that active methods developed in groups and exchange milieus can assist students in improving liberal art education outcomes, especially with a constructivist approach and collaborative practices (Nazaré de Freitas & Assoreira‐Almendra, 2022). In industrial design, researchers suggested pedagogical methods changing from one‐on‐one to peer‐to‐peer teaching and learning and identity change from a studio master to a learning guide (Feast 2020). These pedagogical strategies are also encouraged to practice in humanistic education to improve students’ humanistic capabilities and spirits.…”
Section: Discussionmentioning
confidence: 99%
“…In general design education, researchers suggested that active methods developed in groups and exchange milieus can assist students in improving liberal art education outcomes, especially with a constructivist approach and collaborative practices (Nazaré de Freitas & Assoreira‐Almendra, 2022). In industrial design, researchers suggested pedagogical methods changing from one‐on‐one to peer‐to‐peer teaching and learning and identity change from a studio master to a learning guide (Feast 2020). These pedagogical strategies are also encouraged to practice in humanistic education to improve students’ humanistic capabilities and spirits.…”
Section: Discussionmentioning
confidence: 99%